Empowering Rural Women through Corporate Social Responsibility Initiatives : A Case Study of ExxonMobil’s Economic Impact in Bonorejo Village, Indonesia - Ira Wida Alfiyani; Esa Septian; Junadi (Dinasti Research, 2025)
This study aims to analyze women's empowerment strategies through ExxonMobil's Corporate Social Responsibility (CSR) program in Bonorejo Village, Gayam District. The research approach is qualitative, with a case study method involving observation, structured interviews, and documentation. This study reveals that ExxonMobil's CSR program contributes significantly to women's empowerment through three main stages: awareness, capacity building, and empowerment. Training programs that include technical, managerial, and marketing skills have increased women's self-confidence and economic independence. The study results indicate that the awareness stage has made women aware of their rights and potential so that participants experience increased income and changes in gender status that are more inclusive in the community. This program also helps women actively participate in economic and social activities and household decision-making. The capacity-building stage of this program shows positive results, providing access to relations and assistance from ExxonMobil and the local village government is provided well. At the empowerment stage, this study recommends increasing access to capital, developing digital markets, and further training to support the program's sustainability. With this approach, CSR strengthens women's economic independence and promotes holistic village development.